THE ROLE OF MEDIA CULTURE IN MODERN SOCIETY - Seitova Z.P (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation.The author of the article reveals one of the current topics of our time. As information significantly influences our life choice, the level of our socio- political activity.The role of media culture as a catalyst for many social processes is growing, which undoubtedly influenced not only the development of the country, but also the formation of a new media environment. The fact that media culture changes the world of human relations brings specific features to its consciousness.